Tele-Education in South Africa - Mars, Maurice (Frontiers in Public Health, 2014)
Telemedicine includes the use of information and communication technology for education in the health sector, tele-education. Sub-Saharan Africa has extreme shortage of health professionals and as a result, doctors to teach doctors and students. Tele-education has the potential to provide access to education both formal and continuing medical education. While the uptake of telemedicine in Africa is low there are a number of successful and sustained tele-education programmes. The aims of this study were i) to review the literature on tele-education in South Africa ii) describe tele-education activities at the University of KwaZulu-Natal (UKZ-N) in South Africa and iii) review the development of these programmes with respect to current thinking on eHealth project implementation. Method: a literature review of tele-education in South Africa was undertaken. The development of the tele-education services at UKZ-N from 2001 to present is described. The approaches taken are compared with current teaching on eHealth implementation and a retrospective design-reality gap analysis is made. Results: Tele-education has been in use in South Africa since the 1970s. Several forms of tele-education are in place at the medical schools and in some Provincial Departments of Health. Despite initial attempts by the National Department of Health there are no national initiatives in tele-education. At UKZ-N a tele-education service has been running since 2001 and appears to be sustainable and reaching maturity, with over 1,400 hours of videoconferenced education offered per year. The service has expanded to offer videoconferenced education into Africa using different ways of delivering tele-education. Conclusions: Tele-education has been used in different forms for many years in the health sector in South Africa. There is little hard evidence of its educational merit or economic worth. What it apparent is that it improves access to education and training in resource constrained settings. T